Transformation of the Notary’s Role in Electronic Deed Regulations Based on Digital Technology - Efendi, Wiji Achmat; Sesung, Rusdianto (Journal of Law, Politic and Humanities, 2025)
The rapid development of digital technology has urged the transformation of notarial practice from conventional to digital-based services, particularly in the formulation of electronic deeds. However, the absence of specific regulations regarding the authority and procedures of notaries in creating electronic deeds under Indonesian law has resulted in legal uncertainty. This paper aims to analyze the urgency of regulating electronic deeds in the context of notarial duties and authorities, by focusing on the need to harmonize legal norms with technological advancement. Using a qualitative method based on literature review of previous research and normative legal sources, this study explores three main aspects: the shift in the paradigm of notarial practices in the digital era, the legal vacuum and uncertainty stemming from the lack of regulation, and the structural and ethical readiness of notaries to adopt digital processes. The findings highlight that without a clear legal framework, the implementation of electronic deeds risks inconsistencies in practice, diminished legal protection, and erosion of public trust. It is therefore crucial for the state to revise existing laws and establish adaptive and integrated policies to support the digital transformation of the notarial profession